THE CONFRONTATION BETWEEN THE AUTHORITIES AND THE PEASANTS ON THE TERRITORY OF SOVIET UKRAINE IN THE SECOND HALF OF THE 1940S (ACCORDING TO DOCUMENTS OF THE SECRETARIAT OF PEOPLE’S COMMISSARIAT OF STATE SECURITY – MINISTRY OF STATE SECURITY OF THE UKRAINIAN SSR) - ILNYTSKYI, Vasyl; VASYLENKO, Viacheslav (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The purpose of the article is to reveal the main directions of the confrontation between the authorities and the peasants on the territory of Soviet Ukraine in the second half of the 1940s (according to the documents of the Secretariat of the People’s Commissariat of State Security – Ministry of State Security (NKVD-MDB) of the Ukrainian SSR). The research methodology is based on the principles of historicism, objectivity, comprehensiveness, critical and systematic approaches. General scientific, historical and source-study methods have been used: analytical, logical, synthetic, typological, historical comparative and heuristic. Scientific novelty. The features and information potential of the reporting documents of the NKVD-MDB of the Ukrainian SSR, which are concentrated in the Sectoral State Archive of the Security Service of Ukraine (SSA SSU) in the fund of the Secretariat of the State Police of the Ukrainian SSR-KGB of the Ukrainian SSR, were clarified to reveal the littlestudied problem of the confrontation between the authorities and the peasantry on the territory of the Ukrainian SSR in the second half of the 1940s. Conclusions. Thus, through poor management of agriculture, merciless tax pressure, and deliberate disregard for the needs of the population in the most essential things, the authorities pushed the peasants into desperate conscious and spontaneous resistance. Anti-Soviet and anti-collective farm agitation spread throughout Ukraine as the main form of conscious peasant resistance. Peasants in the western regions of Ukraine also joined the organized armed struggle against national enslavement and the introduction of collective farm slavery. Condemned to hunger and poverty, ordinary people were forced to steal, rob, sabotage, and even kill in order to survive or seek revenge. The mechanism for combating the resulting wave of crime was harsh and inevitable criminal prosecution. The meager and often unreliable in-kind payment for the hard labor in collective farms led to widespread, open sabotage of work. The state’s use of administrative deportation for failing to fulfill the minimum number of workdays forced peasants to make a difficult but clear choice between ungrateful l work on the collective farm and hardship in exile. Keywords: peasantry, famine, Ukrainian SSR, NKVD-MDB, source, research methodology.